Al-Qur'an dalam Okultisme Nusantara (Studi atas Transformasi Ayat al-Qur’an dalam Mantera-Mantera Lokal) - Asep N. Musaddad (Religia, 2017)
This article aims to discuss the transformation of Qur’anic verses into local magical spells in the archipelago. This kind of phenomenon is one of the native’s reception of the Qur’an in the light of occultism, namely the belief in supernatural forces. Started with the preliminary sketch on the occultism in the archipelago, this article explores particularly some representative incantations from Banjarese, Javanese-Using, and Sundanese-Priangan. Modes of transformation and reception as represented in the selected incantations are the major discussion here. The findings lead to the unique picture on how the Qur’anic verses were transformed into several incantations with various modes. It finally represents one of the intersection of Islamic spectrums and local genius in the archipelago.